2021
DOI: 10.3389/fpsyt.2021.674194
|View full text |Cite
|
Sign up to set email alerts
|

One Year Into the Pandemic: A Systematic Review of Perinatal Mental Health Outcomes During COVID-19

Abstract: Obstetric guidelines have rapidly evolved to incorporate new data and research on the novel coronavirus disease (COVID-19), with data on perinatal mental health building over the last year. Our aim in the present manuscript is to provide a systematic review of mental health outcomes in pregnant and postpartum women during the COVID-19 pandemic in the context of neonatal and obstetric guidelines addressing symptoms and complications of COVID-19 during pregnancy, mother-to-neonate transmission, Cesarean-section … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
109
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(130 citation statements)
references
References 131 publications
8
109
1
1
Order By: Relevance
“…[4][5][6] A recently published systematic review of mental health outcomes in pregnant women during the COVID-19 pandemic has also shown that psychological symptoms, such as depressive symptoms and anxiety, are increasing. 7 A stressful life, along with vulnerabilities to stress, causes psychological distress and increases the risk of mental illness, such as depression and anxiety. Given that stress resulting from a severe natural disaster is sudden, while the stress from the COVID-19 pandemic has persisted over time, these types of stress are likely to differ.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] A recently published systematic review of mental health outcomes in pregnant women during the COVID-19 pandemic has also shown that psychological symptoms, such as depressive symptoms and anxiety, are increasing. 7 A stressful life, along with vulnerabilities to stress, causes psychological distress and increases the risk of mental illness, such as depression and anxiety. Given that stress resulting from a severe natural disaster is sudden, while the stress from the COVID-19 pandemic has persisted over time, these types of stress are likely to differ.…”
Section: Introductionmentioning
confidence: 99%
“…However, only 15 (11.1%) Black women were included in this sample (Perzow et al, 2021). Nineteen of the 81 studies included in a systematic review compared mental health outcomes in pregnant or postpartum women before and during the pandemic (Iyengar et al, 2021). Eleven of these 19 studies reported elevated levels of clinically significant mental health symptoms such as depression and anxiety in pregnant or postpartum women during the COVID-19 pandemic (Iyengar et al, 2021).…”
Section: Comparisons Of Psychological Distress Before and During The Covid-19 Pandemicmentioning
confidence: 99%
“…Nineteen of the 81 studies included in a systematic review compared mental health outcomes in pregnant or postpartum women before and during the pandemic (Iyengar et al, 2021). Eleven of these 19 studies reported elevated levels of clinically significant mental health symptoms such as depression and anxiety in pregnant or postpartum women during the COVID-19 pandemic (Iyengar et al, 2021). However, only 5 of the 19 studies were conducted in the United States, and only two of these five studies were conducted with pregnant women (Iyengar et al, 2021).…”
Section: Comparisons Of Psychological Distress Before and During The Covid-19 Pandemicmentioning
confidence: 99%
See 2 more Smart Citations